Pembuatan Perangkap Tikus Semi Otomatis Dengan Sensor Gerak - Nurdi, Mi’rajzul Hudia; Pramudi, Muhammad Indar; Marsuni, Yusriadi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
An effort to minimize the negative impact of using chemicals to eradicate rats, it is necessary to look for other control alternatives using traps. Many conventional mouse traps that are less effective in their use can backfire on themselves. Addressing this problem, the author tried to design a semi-automatic mouse trap combined with sensory (motion). The aim of this research is to make semi-automatic mouse traps and various designs to find out which ones are more effective for trapping mice. The method used in this research is trap control carried out in rice fields. The installation of traps was tested for sensory effectiveness. The results of this research show that the motion sensor installed in the trap detected movement visible in the Android application and was successful in trapping mice.